ANALISIS KESALAHAN MORFOLOGI DALAM PENULISAN MAKALAH MAHASISWA HUKUM EKONOMI SYARIAH IAIN SURAKARTA - Bahaudin Alfiansyah Syafi'i; Ira Khoirun Niha; Silfiyatun Nisaa' (Jurnal Penelitian Humaniora, 2021)
This research aims to find the forms of language errors in the making of papers by students of Islamic Economics Law (HES), in particular class D in the semester VI of the 2019 academic year at the State Islamic Institute of Surakarta. To reach this goal, we employ a combination of descriptive and qualitative methods. We focused on the written errors in the linguistic field of morphology. The data were obtained through the note-taking method. They were then analysed was by making groups of the data, proceed with a presentation of the data, and  verification of the data. The results of the study show 13 kinds of errors in the field of morphology. They are the writing the prefix di- that should be merged into non-merging and vice versa, the writing of the prefix ber-, the writing of prefix me-, the writing of the prefix ter-, the use of suffix -nya, the use of suffix -kan, the combination of the prefix di- with suffix -kan, the writing of prefix me- in combination with suffix -i, the use of prepositions, the writing of the simulphic me -kan, the use of confix ke-an, and the writing of confix per-an. These results indicate that students must continue to learn the rules in scientific writing that refer to the General Indonesian Spelling Guidelines (PUEBI).